(untitled) (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2024)
First-grade students at SDN Sindang Mulya 03 often encounter difficulties in arithmetic. Using appropriate learning resources, such as flash cards depicting concrete objects like pens, tables, chairs, erasers, and books, greatly enhances students’ understanding, aligning with Jean Piaget’s theory of children’s cognitive development. Considering that first-grade students are transitioning from the pre-operational stage to the concrete operational stage, this study aims to determine whether the utilization of flash card media can improve the cognitive abilities of first-grade students at SDN Sindang Mulya 03 in topics related to addition and subtraction of numbers up to 20. The study also investigates whether students’ cognitive abilities improve before and after using flash cards. The research employs an action research approach with two cycles and one pre-cycle meeting, involving 18 first-grade students as participants. The study’s findings demonstrate that the use of flash cards can serve as an alternative method to help students operate numbers up to 20 (in addition to subtraction). This is evidenced by the improvement in students’ scores on evaluation sheets from the pre-cycle, cycle 1, to cycle 2, indicating that the use of flash cards has successfully strengthened the cognitive abilities of first-grade students at SDN Sindang Mulya 03.